2022
DOI: 10.1111/mcn.13368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prelacteal feeds and neonatal introduction of breast milk substitutes on breastfeeding outcomes: A systematic review and meta‐analysis

Abstract: The introduction of fluids other than breast milk during the first few days of life or later neonatal period has been identified as a risk factor for suboptimal breastfeeding (BF) outcomes in numerous studies using varying study designs. However, the relationship between early introduction of fluids other than breast milk and BF outcomes has not been systematically assessed using only prospective studies that can establish temporality, which is critical for determining whether observed associations are causal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 65 publications
0
34
1
3
Order By: Relevance
“…Many studies reported that children who were prelacteal fed are less likely to be exclusively breastfed under six months or to continue breastfeeding throughout the first year of life. Therefore, prelacteal feeding is a risk factor for suboptimal breastfeeding practices worldwide 29 . Importantly, the prevalence of EIBF and prelacteal feeding is inversely correlated in LMICs 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that children who were prelacteal fed are less likely to be exclusively breastfed under six months or to continue breastfeeding throughout the first year of life. Therefore, prelacteal feeding is a risk factor for suboptimal breastfeeding practices worldwide 29 . Importantly, the prevalence of EIBF and prelacteal feeding is inversely correlated in LMICs 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Infants under 6 months of age who are not exclusively breastfed are at significantly higher risk of allcause mortality and infection-related mortality compared to exclusively breastfed infants (Sankar et al, 2015). Prelacteal feeding, that is feeding an infant anything other than breast milk in the first 3 days of life, is associated with higher morbidity and mortality in the first year of life and also earlier cessation of breastfeeding (Nguyen et al, 2020;Pérez-Escamilla et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Infants under 6 months of age who are not exclusively breastfed are at significantly higher risk of all‐cause mortality and infection‐related mortality compared to exclusively breastfed infants (Sankar et al, 2015 ). Prelacteal feeding, that is feeding an infant anything other than breast milk in the first 3 days of life, is associated with higher morbidity and mortality in the first year of life and also earlier cessation of breastfeeding (Nguyen et al, 2020 ; Pérez‐Escamilla et al, 2022 ). Acknowledging the benefits, the WHO and United Nations Children's Fund (UNICEF) recommend initiation of breastfeeding within the first hour of birth, exclusive breastfeeding for the first 6 months of life, and continued breastfeeding until 2 years of age or beyond (WHO & UNICEF, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Findings call for urgently addressing the need for well‐trained health providers and counseling programmes to provide guidance to parents and caregivers on common baby behaviours and how to properly cope with them while protecting breastfeeding. Pérez‐Escamilla and colleagues (Pérez‐Escamilla et al, 2022), assessed whether introduction of prelacteals (either milk‐based or water‐based fluids introduced during the first 3 days of life) and BMS nowadays also referred to as commercial milk formulas (WHO & UNICEF, 2022) between 4 days and 4 weeks postpartum undermine breastfeeding success. The authors carried out a systematic review and meta‐analysis, including only prospective studies, allowing them to determine the temporal directionality of the associations.…”
mentioning
confidence: 99%
“…The aim of this supplement is to bring together the most updated evidence on challenges to improve breastfeeding practices worldwide and to identify promising policies and programmes to protect, promote and support breastfeeding on a large scale. New evidence on the influence of baby behaviours and caregiver's infant feeding decisions during the first 6 months of life, is described by Vilar-Compte and colleagues in a systematic review (Vilar-Compte, Pérez-Escamilla, et al, 2022). The systematic review which included studies with different designs (descriptive, crosssectional, prospective, and quasi-experimental), provided consistent evidence that baby behaviours such as infant crying and fussiness are critical in shaping caregiver's decisions on infant feeding practices.…”
mentioning
confidence: 99%